Deradikalisasi Pendidikan Islam,Peran Guru dan Kurikulum Madrasah dalam Mencegah Radikalisme di Indonesia - Marzuqi, Ahmad; Aziz, Imam Nur (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This study analyzes the contribution of madrassas in developing religious moderation in Indonesia in the millennial era, especially in response to the increase in radicalism and intolerance among students. Islamic education in madrasas has been considered to be still oriented towards cognitive aspects, so it is not optimal in shaping the character and spirituality of students. With a descriptive qualitative approach, this study uses primary data from the phenomenon of radicalism in the school environment, as well as secondary data from literature related to radicalism and religious education. The results of the study show that madrassas have a strategic role in forming a moderate and inclusive understanding of religion through the integration of moral and social values in the Islamic Religious Education (PAI) curriculum. However, challenges still arise in the form of the dominance of textual approaches in learning, the potential for intolerance in textbooks, as well as the influence of the external environment and weak school policies in counteracting radicalism. This research emphasizes the importance of curriculum reorientation and the active role of teachers in instilling the values of tolerance, dialogism, and contextual religious understanding to prevent the development of radical ideas among madrasah students. Thus, madrasas are expected to be at the forefront of building the character of the young generation who are moderate, tolerant, and nationalistic.